Modifying SnS2 With Carbon Quantum Dots to Improve Photocatalytic Performance for Cr(VI) Reduction - Li, Weidong; Qiu, Jianping; Jin, Haihong; Wang, Yuanyuan; Ma, Dandan; Zhang, Xinxiang; Yang, Huayun; Wang, Fangyuan (Frontiers in Chemistry, 2022)
The photoreduction for hazardous Cr(VI) in industrial wastewater has been considered as a “green” approach with low cost and easy-to-go operation. SnS2 is a promising narrow bandgap photocatalyst, but its low charge carrier separation efficiency should be solved first. In this work, N-doped carbon quantum dots (CQDs) were prepared and loaded onto SnS2 nanoparticles via an in-situ method. The resulting composite samples (NC@SnS2) were characterized and their photocatalytic performance was discussed. SnS2 nanoparticles were obtained as hexagonal ones with bandgap of 2.19 eV. The optimal doping level for NC@SnS2 was citric acid: urea:SnS2=1.2 mmol:1.8 mmol:3.0 mmol. It showed average diameter of 40 nm and improved photocatalytic performance, compared to pure SnS2, following a pseudo-first-order reaction with kinetic rate constant of 0.1144 min-1¬¬. Over 97% of Cr(VI) was photoreduced after 30 min. It was confirmed that modification of SnS2 with CQDs can not only improve the light harvesting ability, but also stimulate the charge separation, which therefore can enhance the photoreactivity of SnS2 towards Cr(VI) reduction. The excellent stability of NC@SnS2 indicates it is promising to be practically used in industrial wastewater purification.